HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN PROSES PENYEMBUHAN PADA PENDERITA KUSTA DI KABUPATEN BENGKALIS RIAU - Tukiman Tukiman; Mukhlis Mukhlis (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACTLeprosy is a contagious disease which causes a very complex problem. Such a problem is not only a medical aspect but also it spreads to social, economic and cultural problem and comfort. Leprosy, up till now, is still frightened by all levels of society, families and including partly paramedics and medical officials. This matter is caused by the lack of  knowledge and disbelief toward leprosy. This research has a purpose to learn the relationship between the knowledge and the families’ responses with the healing process to the leprosy patients in the regency of Bengkalis Riau 2010. This kind of research has an analytic characteristic with the approach of cross sectional. The population in this research is all the family members of leprosy sufferers with the sample of 40 persons out of 97 persons. The method of sample selection is the cluster sample and uses chi-square analysis. The result of the research indicates that the respondents’ knowledge is in the medium category (67.5%), the good category attitude (52.5%) and recovery process of medium category (77.5%). It is found out that there is a significant correlation between the level of knowledge and the curative process toward the leprosy sufferers (P=0.007) and there is no significant correlation between the level of attitudes and the curative process upon leprosy sufferers (P=1.000).                It is suggested that health officials increase the supervision and health promotion to the family members of leprosy sufferers toward leprosy, contagion, therapy and the side effects of medication and it is also expected that families will pay more attention and give moral support to the leprosy sufferers in order that they will have more self confidence and perseverance in undergoing medical treatment. Kata Kunci : Keluarga, penyembuhan penyakit kusta.